2006
DOI: 10.1128/jvi.80.7.3285-3292.2006
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Novel Vesicular Stomatitis Virus Glycoprotein Variants from a Peptide Insertion Library for Enhanced Purification of Retroviral and Lentiviral Vectors

Abstract: The introduction of new features or functions that are not present in an original protein is a significant challenge in protein engineering. For example, modifications to vesicular stomatitis virus glycoprotein (VSV-G), which is commonly used to pseudotype retroviral and lentiviral vectors for gene delivery, have been hindered by a lack of structural knowledge of the protein. We have developed a transposon-based approach that randomly incorporates designed polypeptides throughout a protein to generate saturate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 51 publications
1
46
0
Order By: Relevance
“…As a first step to reach that goal, we attempted to display tumor-targeting ligands on a replication-competent VSV. Our approach was to identify novel sites in the G protein of VSV (VSV-G) to insert and display foreign peptides without compromising viral replication kinetics or oncolytic efficacy.Several previous attempts to insert foreign peptides into VSV-G were conducted purely in the interest of lentivirus targeting and purification (17)(18)(19)(20). Additionally, one previous study identified a site that could tolerate insertion of a 16-residue peptide that was an antigenic HIV epitope (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a first step to reach that goal, we attempted to display tumor-targeting ligands on a replication-competent VSV. Our approach was to identify novel sites in the G protein of VSV (VSV-G) to insert and display foreign peptides without compromising viral replication kinetics or oncolytic efficacy.Several previous attempts to insert foreign peptides into VSV-G were conducted purely in the interest of lentivirus targeting and purification (17)(18)(19)(20). Additionally, one previous study identified a site that could tolerate insertion of a 16-residue peptide that was an antigenic HIV epitope (21).…”
mentioning
confidence: 99%
“…Several previous attempts to insert foreign peptides into VSV-G were conducted purely in the interest of lentivirus targeting and purification (17)(18)(19)(20). Additionally, one previous study identified a site that could tolerate insertion of a 16-residue peptide that was an antigenic HIV epitope (21).…”
mentioning
confidence: 99%
“…Both rational ligand insertion and random peptide display require knowledge of insertion sites that do not compromise envelope function and are exposed on the protein surface for receptor binding Roth, 2002, 2003;Bupp et al, 2005Bupp et al, , 2006. However, if information on such permissive insertion sites is not available, it can be also newly obtained by transposon-based scanning of envelope proteins (Rothenberg et al, 2001;Yu and Schaffer, 2006b). The insertion and excision of a bacteriophage Mu transposase cassette into cDNA encoding the Moloney murine leukemia virus (MoMLV) envelope protein resulted in the duplication of five amino acids at a random insertion site.…”
Section: Cell Receptor-specific or Transductional Targetingmentioning
confidence: 99%
“…Subsequent selection of the resulting mutant library for the ability to mediate viral replication in culture led to the identification of multiple sites permissive for the five amino acid insertion (Rothenberg et al, 2001). More recently, a 13 amino acid sequence, including a 6 histidine peptide, was randomly inserted into envelope proteins of vesicular stomatitis virus (VSVG), and the selection of the resulting library for the ability to mediate viral replication in culture and for the capacity to bind an immobilized metal column led to the identification of several permissive insertion sites on the outer surface of VSVG (Yu and Schaffer, 2006b). These hexa-histidine mutant VSVG envelopes offer the capability for rapid and highly effective purification of viral vector.…”
Section: Cell Receptor-specific or Transductional Targetingmentioning
confidence: 99%
“…These PCR fragments were cloned into TOPO sequencing vectors and sequences were verified by DNA sequencing. The DNA sequence containing GFP was rescued off the plasmid clPIT-GFP (Yu and Schaffer 2006) using the oligonucleotides 59-GGGAATTCCATATGCTACCGGTCGCC-39 Discovery of a molecular chaperone filament www.proteinscience.org 631 (forward primer) and 59-TCCGTTTAAACTCGAGATCTGAGT CC-39 (reverse primer) with NdeI (59) and XhoI (39) restriction sites. a PFD, g PFD, and GFP were subcloned into pET-19, while b PFD was subcloned into pET-30.…”
Section: Plasmid Constructionmentioning
confidence: 99%